Place Attachment between Public Space, Identity and Citizenship. Case Study about a Chilean Public Square - Rojas Mora, Paloma (2024)
Objective. To explore the meanings and uses associated to a public square in the city of Temuco, Chile. Method. It is a qualitative study, with a case study design. For data collection, situated interviews, participant observations, online surveys, and in-depth interviews with users of the square were applied in three successive stages. 211 volunteers between the ages of 18 and 65 participated in the study. Results. The main results show that there are differences linked with the uses of the square and the meanings associated with the place according to gender, age, time of residence and political tendency.